2000
DOI: 10.1021/bi000724n
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+-Dependent Compaction and Folding of Yeast tRNAPhe and the Catalytic Domain of the B. subtilis RNase P RNA Determined by Small-Angle X-ray Scattering

Abstract: We apply synchrotron-based small-angle X-ray scattering to investigate the relationship between compaction, metal binding, and structure formation of two RNAs at 37 degrees C: the 76 nucleotide yeast tRNA(Phe) and the 255 nucleotide catalytic domain of the Bacillus subtilis RNase P RNA. For both RNAs, this method provides direct evidence for the population of a distinct folding intermediate. The relative compaction between the intermediate and the native state does not correlate with the size of the RNA but do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 33 publications
9
127
0
Order By: Relevance
“…14,38,41 The Kratky plot exhibits a plateau at the high Q region for particles with extended conformation, since the Debye function for scattering from a Gaussian coil has a limiting behavior of Q −2 at high Q. However, for globular/compact particles I(Q).Q 2 values will decrease at high Q since I(Q) should vary as Q −4 for them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,38,41 The Kratky plot exhibits a plateau at the high Q region for particles with extended conformation, since the Debye function for scattering from a Gaussian coil has a limiting behavior of Q −2 at high Q. However, for globular/compact particles I(Q).Q 2 values will decrease at high Q since I(Q) should vary as Q −4 for them.…”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively used for the characterization of tertiary structural changes of proteins in solution, protein-protein interactions, micellization of block copolymers, 30 protein aggregation, quaternary structures 25,40,41 and the thermodynamics and kinetics of protein and RNA folding. 14,20,40 As shown by Guinier 16 the low Q region (Q = 4π/λ sin θ is the magnitude of the scattering vector where 2θ is the scattering angle and the λ is the wavelength of the X-rays) of the SAXS data can be approximated to be a Gaussian,…”
Section: Small Angle X-ray Scatteringmentioning
confidence: 98%
“…The oligomerization state and the shape of the B. subtilis RNase P holoenzyme are determined by synchrotron SAXS (Fig+ 1)+ The high flux of the synchrotron radiation permits the measurement to be carried out at micromolar P RNA concentrations in a few seconds+ Two SAXS-derived parameters are used to deduce the oligomerization state of P RNA in the absence and presence of the P protein, the scattering intensity at zero angle (I 0 ) and the pair distance distribution (P(r); Cantor & Schimmel, 1980)+ I 0 is directly proportional to the molecular weight of the complex, whereas P(r) is the sum of all distance pairs within the complex+ In the absence of the P protein, the I 0 ratio (5+6 6 0+6) of P RNA and yeast tRNA Phe at the same weight concentration (0+1-1 mg/mL) is proportional to their molecular weight ratio (5+4)+ Yeast tRNA Phe has been shown conclusively to be mono-dispersed under these conditions (Fang et al+, 2000)+ Hence, this result shows that P RNA in the absence of P protein is a monomer under our experimental conditions+…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 94%
“…Small-angle X-ray scattering of P RNA with and without P protein+ A: Scattering profile of P RNA with (red trace) and without (black trace) P protein in 20 mM Tris-HCl, pH 8, 10 mM MgCl 2 , 0+1 M NH 4 Cl, 0+3 mg/mL RNA (2+4 mM), 37 8C+ The unmodified yeast tRNA Phe is used as a monomer standard (Fang et al+, 2000)+ B: P(r) functions of P RNA and the holoenzyme+ C: Scattering of P RNA with (black trace) or without (blue trace) 0+1 M NH 4 Cl+ The P(r) functions are shown in the insert+ P protein complex reconstituted at 1:1 RNA-protein, (1+7 6 0+2) ϫ 10 Ϫ3 , is twofold higher than the I 0 of P RNA in the absence of the P protein, (0+9 6 0+1) ϫ 10 Ϫ3 (Fig+ 1A)+ The scattering profiles cross over at high Q, consistent with oligomerization of P RNA in the holoenzyme+ Because P RNA is ;10 times heavier than P protein and RNA has an approximately fivefold higher X-ray scattering signal than protein, the observed I 0 is almost entirely derived from the scattering from P RNA+ The P(r) function of the holoenzyme has two times more distance pairs compared to those of the P RNA alone, as expected for the formation of a complex containing two P RNA molecules (Fig+ 1B)+ On the basis of the previous determination of the 1:1 stoichiometry of the P RNA and P protein in the holoenzyme under similar conditions (Talbot & Altman, 1994a;Niranjanakumari et al+, 1998a), we conclude that the B. subtilis holoenzyme contains two P RNA and two P protein subunits+ The concentration of P RNA used in the SAXS experiments ranges from 0+12-0+5 mg/mL or 1-4 mM+ These concentrations lie within the range of those used in the studies of catalytic activity and stability of the holoenzyme+ Interestingly, the scattering profile of P RNA without the P protein shows considerable variation in the absence and the presence of monovalent ions, 0+1 M NH 4 Cl (Fig+ 1C) or 0+1 M KCl+ In contrast, this concentration of monovalent ions has no effect on the scattering profile of the holoenzyme, although the dimerization decreases at higher concentrations of monovalent ions (data not shown)+ The native structure of P RNA is composed of two independently folding domains that are connected through two phosphodiester bonds (Loria & Pan, 1996;Fang et al+, 1999)+ The variation in the scattering data of the P RNA monomer at different solution conditions may be explained by a difference in the relative orientation of the two domains (see Discussion)+…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
“…The divalent cation Mg 2ϩ is especially important for the structure and function of nucleic acids (1, 2, 5, 9-12). It has been suggested that divalent cations (e.g., Mg 2ϩ ) may induce an attractive potential that mediates nucleic acid collapse through counterion-correlation effects (15,36,39,40). Other theoretical approaches have suggested that significant attraction in water occurs only for cations of higher charge (Ն3ϩ) (13).…”
Section: High Concentration Of Monovalent Cation Relaxes the Tetheredmentioning
confidence: 99%